Building Students' Reading Habits through Literacy Learning Models as an Effort to Build Young Citizens' Character - Retno Kurnia Saputri; Aim Abdulkarim (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Reading plays an important role in building a literate generation that is able to improve academic skills, broaden horizons and maintain local cultural identity. However, the low interest in reading in Indonesia, especially among students, is a big challenge. Internal factors, such as student motivation, and external factors, such as family and school support, are highly influential. Strategies such as reading for pleasure, edutainment and the School Literacy Movement are effective in fostering a reading culture as well as shaping students' characters, such as honesty, empathy and critical thinking. Challenges in implementation include limited reading materials, teacher training, technology support and collaboration with the community. Strategic steps, such as enrichment of reading materials, intensive teacher training and community involvement, are needed to overcome them. With good literacy, students can think critically, have character and contribute positively. This research uses a qualitative approach through a literature study to examine the importance of literacy culture.